Physicochemical and Sensory Characteristics of “Terong Asam” (Solanum ferox Linn) Dry Sweetmeat at Various Concentrations of Sugar - Dewi, Yohana S Kusuma; Rosanti, Ninda Ima; Rahayuni, Tri (Journal of Agri-Food Science and Technology, 2022)
Solanum ferox Linn is one of the local agricultural products. Its local name is “terong asam”, the plant's shape is like eggplant but the fruit is round, orange with ripe and sour taste. The problem is that the fruit is easily damaged if left in its fresh. One of the innovations to increase the shelf life is to process it into processed dry sweetmeats. However, the amount of sugar that produces the best physicochemical characteristics of “terong asam,” dry sweetmeats is currently unknown. This study aims to obtain the concentration of sugar that produces the best physicochemical and sensory characteristics of “terong asam,” dry sweetmeats. The research design used was a randomized block design with one treatment, namely concentration of sugar, which consisted of 4 treatments and 6 replications. Analysis of physicochemical data using ANOVA (Analysis of Variance) and Honest Significant Difference (HSD) Test with a level of 5% significantly. Sensory data were analyzed by Kruskal Wallis test. Determination of the best treatment using the effectiveness index test. The results showed that the production “terong asam,” dry sweetmeats is recommended by using a 50% sugar concentration which the best sensory physicochemical characteristics of the sweets, namely water content (13.28%), pH (5.08), yield (26.49%), vitamin C (8.7mg/100g) with sensory characteristics of colour (3.17), taste (2.67), aroma (3.30), texture (3.20).